Effect of Impurities in Supercritical CO2 Environment on Steel Corrosion Behavior – an Overview - Widianto, Shilla Rizqi; Soedarsono, Johny Wahyuadi; Riastuti, Rini; Munir, Badrul (Journal of Materials Exploration and Findings, 2024)
Carbon capture, utilization, and storage (CCUS) technology is one of the available technologies to reduce presence of greenhouse gasses. Implementation of CCUS technology strongly relates with the CO2 transportation from the capturing facility to the storage in the geological reservoir. The most economical method for large-scale and long-distance CO2 transportation is using pipeline in supercritical phase. Moreover, presence of impurities such as water, O2, SO2, H2S, NO2 may cause detrimental effect towards carbon steel pipeline. This paper intends to provide an initial information for supercritical CO2 pipeline material selection, which review and summarize existing research on corrosion under supercritical CO2 environment. This paper present environment categorization in supercritical CO2 stream, impurities effect toward sample, as well as brief discussion about corrosion evaluation method.